Optimal level, Partial Speed of Adjustment and Determinants of Corporate Cash Holding: Evidence from MENA Countries - Raghibi, Abdessamad; Thanh, Cuong Nguyen; Oubdi, Lahsen (UI Scholars Hub, 2021)
This paper investigates the existence of an optimal cash level, speed of adjustment, and cash holding determinants. The threshold regression and dynamic model were used in this study on four MENA countries from 2007 to 2018. The findings show there is a nonlinear relationship between cash level and firm’s value which is consistent with the trade-off theory. Furthermore, our study confirms that firms holding cash above the optimal level of having a lower speed of adjustment than the firms with cash levels below the optimal level with size, growth, and net-working capital being key corporate cash determinants. Our results extend the theoretical implications of the trade-off theory to MENA countries and would help corporate policymakers to adjust their cash levels within the thresholds’ levels to maximize their firm value.